2014
DOI: 10.1016/j.neuron.2014.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Segregation of Tactile Input Features in Neurons of the Cuneate Nucleus

Abstract: SummaryOur tactile perception of external objects depends on skin-object interactions. The mechanics of contact dictates the existence of fundamental spatiotemporal input features—contact initiation and cessation, slip, and rolling contact—that originate from the fact that solid objects do not interpenetrate. However, it is unknown whether these features are represented within the brain. We used a novel haptic interface to deliver such inputs to the glabrous skin of finger/digit pads and recorded from neurons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(108 citation statements)
references
References 46 publications
(60 reference statements)
5
95
0
4
Order By: Relevance
“…In their study, participants were able to estimate the length of the motion path of the object on the basis of the simulated vibrations, which required inferring the motion kinematics. An integration of slip-induced vibrations with other tactile motion cues would further support the emerging view of submodality convergence in the tactile system (Jörntell et al 2014;Saal and Bensmaia 2014).…”
Section: Vibrations As a Cue To Tactile Speedmentioning
confidence: 64%
“…In their study, participants were able to estimate the length of the motion path of the object on the basis of the simulated vibrations, which required inferring the motion kinematics. An integration of slip-induced vibrations with other tactile motion cues would further support the emerging view of submodality convergence in the tactile system (Jörntell et al 2014;Saal and Bensmaia 2014).…”
Section: Vibrations As a Cue To Tactile Speedmentioning
confidence: 64%
“…Prior research has shed light on mechanical signals generated during object palpation or manipulation, the transduction of such signals into neural signals, and the salience of different contact-generated stimuli. It has been shown that the responses of somatosensory neurons should be understood in light of perceptual functions that integrate input from several tactile submodalities (1,2).…”
mentioning
confidence: 99%
“…Another recent study systematically tested haptic features, such as contact initiation and cessation, slip, and rolling contact, in glabrous cat skin (Jörntell et al 2014) and clearly demonstrated that each haptic feature was distinctively represented by a combination of DCN neuronal activities. The authors analyzed 10 different periods between 15 and 150 ms after stimulus onset and showed that a linear classification of haptic features was evident even at 30 ms; the linear classification was based on the number of spikes in short time windows (bins) of 5-10 ms.…”
Section: Alteration Of Firing Pattern By Stimulus Featuresmentioning
confidence: 96%
“…When the stimulus features change, the firing pattern changes due to subtle differences in the relative timing of spikes in individual tactile afferents. Indeed, some previous studies have reported that the activities of DCN neurons change depending on stimulus features (Castiglioni and Kruger 1985;Jörntell et al 2014); however, there are no numerical evaluations of the firing patterns (temporal structure of spike trains) of individual neuron in these studies. In a rat study, controlled air-jet stimuli administered in different directions were applied to the hairy skin and directional differences in the neuronal responses were detected by visual inspection (Castiglioni and Kruger 1985).…”
Section: Alteration Of Firing Pattern By Stimulus Featuresmentioning
confidence: 99%